Sustainable Organising Pod: Back-to-the-land Movement - Maria Ehrnström-Fuentes; Stefano Antonioli; Oscar Vesternäs; Siiri Markkanen (2022)
The podcast deals with the back-to-the-land movement and as our guest we had the honor to do an interview with Mathias Handley from Sweden who had quite recently done a drastic change in his lifestyle and moved to the countryside with his wife after living 40 years in the heart of the capital of Sweden, Stockholm. According to Mattias, they knew neither much about the place they were moving to, nor about the new lifestyle they were stepping into, but they have loved pretty much every part of it. The interview with Mattias gives a great insight into the topic, sharing the emotions he felt day by day learning to run a farm, enjoying the food he produced and seeing his new business grow. When asking about what everyone can do in their lives if they do not want to make such an extreme change in the lifestyle that Mattias and his wife have been doing, Mattias was telling that everyone can begin with something, and it is the small actions that actually count. As an example, he was encouraging that we all could start with planting something we find funny and interesting. **This material was produced by students in the course Sustainable Organising at Hanken School of Economics in the spring term of 2022. The group work assignment of the course was to design a podcast show and produce an episode about a topic related to sustainable organising. The interviews were done in February 2022. ***
Keywords: sustainable agriculture; sustainable living; degrowth; alternative movements; cultural sustainability